Application of non-operative management protocol in pediatric blunt splenic injuries with other associated injuries - Fahiem-Ul-Hassan, Mir; Mufti, Gowhar N.; Buch, Mudassir H.; Baba, Aejaz A.; Bhat, Nisar A. (International Surgery Journal, 2019)
Background: Non-operative management (NOM) has become the standard of care for isolated blunt splenic injuries with satisfactory success rates. However, literature is scarce about the non-operative management of blunt splenic injuries (BSI) with other associated injuries (OAI). The main aim of this study is to assess the applicability of protocol-based NOM in BSI with OAI. Methods: Protocol based resuscitative algorithm was followed for the management of patients with BSI and OAI. NOM was taken up in those patients who were hemodynamically stable and was not attempted in patients who remained hemodynamically unstable or developed hemodynamic instability even after the resuscitative efforts. The data was collected and analyzed. Results: Forty patients with the mean age of 7.05±3.9 years were studied. Fall from height formed the commonest mode of injury. The mean AAST grade was 2.55. The most common association was a left lung contusion (20%). Fifteen patients presented with shock among which two failed the protocol-based resuscitative efforts and were hence explored. One of the patients had lung contusion and the other dorsal vertebral fractures (3rd and 4th). Another patient with mesenteric tear and delayed hemorrhage was operated. Two other patients underwent surgical interventions for bowel perforation and fracture of right femur respectively. Spleen was preserved in both of these patients. Though, the NOM was successful in overall 87.5% patients, spleen specific success rate was 92.5%. Conclusions: Application of protocol-based NOM in patients with BSI with OAI is highly successful if instituted in properly selected patients especially those with low grades of injury and also in those with delayed presentation.